Влияние моноксида углерода и сероводорода на трансмембранный ионный транспорт - Гусакова С. В. Светлана Валерьевна; Ковалев И. В. Игорь Викторович; Бирулина Ю. Юлия; Смаглий Л. В. Людмила Вячеславовна; Петрова И. В. Ирина Викторовна; Носарев А. В. Алексей Валерьевич; Алейник А. Н. Александр Никонорович; Орлов С. Н. Сергей Николаевич (2017, 2017)
Заглавие с экрана